2006
DOI: 10.1002/ange.200504210
|View full text |Cite
|
Sign up to set email alerts
|

Strukturempfindlicher und selbstassoziierter helicaler Pyrenstapel auf Basis der DNA‐Architektur

Abstract: Der helicale π‐Stapel aus fünf pyrenmodifizierten Uridineinheiten zeigt eine ausgeprägte Fluoreszenzverstärkung, die empfindlich auf Basenfehlpaarungen reagiert. Die Fluoreszenz ist deutlich sequenzabhängig, weshalb der Stapel als strukturempfindliche Sonde für DNA fungieren kann.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
3

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 38 publications
0
23
0
3
Order By: Relevance
“…In these studies, DNA or RNA were used as structural scaffolds for the helical arrangement of pyrenes. In contrast to these intrastrand helical stacks along a DNA or RNA backbone, [24,25] the present system describes the self-organization of two non-nucleosidic oligopyrene strands in an interstrand helical stack. An Amber-mimized model [26] (Figure 4) shows an overall right-handed helical arrangement of the twisted pyrene rings, which is in agreement with the experimental observations.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…In these studies, DNA or RNA were used as structural scaffolds for the helical arrangement of pyrenes. In contrast to these intrastrand helical stacks along a DNA or RNA backbone, [24,25] the present system describes the self-organization of two non-nucleosidic oligopyrene strands in an interstrand helical stack. An Amber-mimized model [26] (Figure 4) shows an overall right-handed helical arrangement of the twisted pyrene rings, which is in agreement with the experimental observations.…”
Section: Methodsmentioning
confidence: 96%
“…Comparison of these data, together with the already described values obtained at 260 nm, showed excellent agreement (Table 2), thus suggesting a high degree of cooperativity among the different sections of the hybrid. [23] The arrangement of pyrene molecules covalently linked to the sugar backbone in RNA [24] and to base residues in DNA [25] was published recently. In these studies, DNA or RNA were used as structural scaffolds for the helical arrangement of pyrenes.…”
Section: Methodsmentioning
confidence: 99%
“…[15] It has also been reported that the shift of the excimer emission band can be used as a signal to detect hybridization, as the excimer fluorescence could redshift or blue-shift upon hybridization by the interstrandstacked pyrenes. [16] Although both monomer and excimer emission of pyrene-labeled probes has been investigated in detail, the often complex response depends on the structure of the probe.…”
Section: Introductionmentioning
confidence: 99%
“…This means that for some DNA duplexes the fluorescence quenched by the flanking C/G base pair differs little from that of a single stranded probe. [12][13] To overcome this disadvantage, pyrene excimer emission instead of monomer emission has been explored for monitoring RNA and DNA hybridization, [14][15][16][17][18][19][20][21] as pyrene-excimer emission is less sensitive to quenching by nucleobases than monomer emission.…”
Section: Introductionmentioning
confidence: 99%
“…pyrene pseudonuleotides have been utilized as sensitive hybridization probes. [6] Studies of charge transfer in DNA have made use of pyrene-modified nucleosides.…”
Section: Introductionmentioning
confidence: 99%